Habilidade de cuidado, sobrecarga, estresse e coping de cuidadores familiares urbanos e rurais de pacientes em tratamento oncológico - Siqueira, Fernanda Duarte (2019)
This study aims to analyze the relationship of care ability of urban and rural family caregivers of patients undergoing oncologic treatment with overload, stress and coping strategies. This is a cross-sectional study, developed with 222 urban and rural family caregivers, from April 2017 to May 2018, performed at the oncology service of a University Hospital of Rio Grande do Sul. Data collection was used a demographic and clinical questionnaire for patients, sociodemographic questionnaire of caregivers and characteristics of care provided, Care Skills Inventory, Burden Interview Scale, Perceived Stress Scale and COPE Brief. The final sample was divided into two groups, according to the place of residence of family caregivers: urban area (n = 163) and rural area (n = 59). The qualitative variables were presented by the distribution of absolute and relative frequencies and the quantitative variables, in measures of central tendency and variability. Pearson's correlation, Student t and Mann-Whitney tests were performed according to the distribution of the data, at significance level ≤5%. The research was approved by the Research Ethics Committee (Opinion 1,977,316). The results showed that among the patients, men predominated, mean age of 67.2 years, with an average diagnosis time of 26.8 months, with cancer of the digestive tract and moderate dependence. The majority of the urban caregivers were women, aged between 48 and 76 years, with education between 7 and 13 years of study, with companion, who do not exercise paid activity at the moment, with income up to three minimum wages, that reside with the person cared for and other family members. They have been in care for less than five months, full time, with the assistance of third parties and have previous experience in caring. Most caregivers of children aged 48 to 76 years, low schooling (age study), with the companion, who do not engage in paid activity, low income, who reside with the family patient and other relatives. The time of care was over eight months, with full-time follow-up, with the help of third parties and without previous experience. It was found that urban caregivers performed greater ability for total care, knowledge, courage and patience. Urban caregivers are charged moderately, while those responsible are not overloaded. The greater perception of stress in urban caregivers. A similarity was identified between urban and rural managers without the use of problem-focused coping strategies. Between care ability and stress, it was found to be negative and moderate in rural caregivers. The relationship of care capacity and overload was found in statistically significant statistic more in urban caregivers, not understanding interpersonal relationship and perception of self-efficacy. Between the coping and a care skill identified was positive and moderate in the confrontation focused without problem no knowledge among the urban. Nursing's attention to caregiver support can take the singularities of each life context seriously, as these singularities can influence differently care, overload, stress and coping strategies.